GROSS PATHOLOGY AND HISTOPATHOLOGY DESCRIPTION OF IMMUNE ORGANS OF BALI DUCK AFTER EXPERIMENTAL INFECTION WITH AVIAN ORTHOAVULAVIRUS 1 TABANAN-1/ARP/2017 ISOLATE - Al Ma'arif, M. Farhan; Adi, Anak Agung Ayu Mirah; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana, 2022)
This research aims to determine the gross pathological and histopathological changes of the thymus, bursa of Fabricius, and spleen of bali ducks infected with newcastle disease virus or Avian orthoavulavirus 1 Tabanan-1/ARP/2017 isolate. This research used 15 male bali ducks aged one week. After the acclimatization period for two weeks and the measurement of ND antibody titer in duck serum showed results below 2 3 HI units, 10 ducks were infected with AOAV-1 Tabanan-1/ARP/2017 isolate at a dose of 0.5 ml/2 7 HA units intraocularly (P 1 ) and 5 other ducks as the control (P 0 ) were given 0.5 ml of phosphate buffered saline by the same route. Then necropsy was performed on the dead ducks and gross pathology examination was performed on its immune organs. That organs were processed and stained for Hematoxylin-Eosin, then performed histopathology examination. The results showed that infection with AOAV-1 Tabanan-1/ARP/2017 isolate in bali ducks could cause gross pathological changes in the form of necrotic foci lesions in the spleen and atrophy in the thymus. Meanwhile, the histopathological appearance showed severe depletion of lymphoid cells in the thymus and bursa of Fabricius, and mild lymphoid cell depletion in the spleen.